Dye removal from textile wastewater using scoria-based of vertical subsurface flow constructed wetland system - Ribika Etana; Kenatu Angassa; Tolesa Getu (Scientific Reports, 2025)
Abstract Textile wastewater poses significant risks if discharged untreated, especially due to the presence of synthetic dyes, salts, and heavy metals. As a result, constructed wetlands have emerged as a promising solution for sustainable textile wastewater management. In this context, this study evaluates a micro-scale vertical subsurface flow constructed wetland (VSSFCW) for treating textile wastewater. Specifically, the experimental setup consisted of two microcosm units, each with a depth of 32 cm and a diameter of 24 cm, which were filled with scoria media. One unit was planted with Vetiver grass, while the other was left unplanted. Furthermore, the experiment was conducted with a hydraulic retention time of 3 days. Additionally, the scoria media was characterized using FTIR, SEM, XRD, CEC, and pH analyses, which revealed notable changes in both functional groups and surface morphology. The scoria was found to have a CEC of 12 meq/100 g and a pH of 8.86, both of which facilitated pollutant removal. Moreover, the textile wastewater that was fed into the VSSFCW systems contained dye concentrations ranging from 39.41 to 45.29 mg/L throughout the study period. As a result of this setup, the dye removal efficiency in both wetland cells increased over time. Notably, the VSSFCW planted with Vetiver grass achieved a higher dye removal efficiency (84%) compared to the unplanted system (80%). These findings, therefore, demonstrate that the VSSFCW consistently meets wastewater standards, representing a low-cost, decentralized solution to address textile pollution, especially in developing countries like Ethiopia. In conclusion, the synergy between the scoria media and Vetiver grass proved highly effective in treating textile wastewater.